Influence of specially directed exercises on separate functions of sensor-based systems of pupils of junior classes - Irina Maslyak (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to define dynamics of separate functions of sensor-based systems of children of primary school age as a result of specially directed physical exercises. Material and Methods: 306 pupils of the 1st - 3rd classes of a comprehensive school of Kharkov took part in the research. The following methods were used: theoretical analysis of scientifically methodical literature, pedagogical experiment, pedagogical testing, methods of mathematical statistics, and methods of determination of separate parameters of touch functions (perimetry, acumetry, esthesiometry and others). Results: the assessment of a functional condition of visual, acoustical, vestibular, tactile analyzers and visual-motor reaction is carried out; the age distinctions in indicators are considered; the extent of influence of specially directed exercises on separate functions of the studied sensor-based systems is defined. Conclusions: the positive influence of specially directed exercises on a condition of separate functions of vestibular, acoustical, visual and tactile analyzers at pupils of junior classes is established.